LARGE-SCALE MINING IN LUZON, PHILIPPINES: ASSESSMENT OF THE MANDATED SOCIAL RESPONSIBILITY TO THEIR HOST COMMUNITIES - Jackie Lou O. Raborar; Email: jackielou.raborar.gs@ust.edu.ph) Elizabeth O. Recio (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
In this global market, the demand and competition for mining products are very high. However, the adverse impact on the environment and society has become very prevalent. In the World Bank report, there are social issues that still unaddressed; there is the issue of how the benefits are allocated within the host communities, and it’s a challenge to mining companies to behave responsibly especially with their relationship to the host communities. United Nations has committed to “leaving no one behind” in an effort to help countries promote inclusive growth and achieve the Sustainable Development Goals (SDGs). The Philippine government, through the Department of Environment and Natural Resources (DENR), has established the Republic Act No. 7942, ‘or the Philippine Mining Act of 1995. The Development of Mining Communities has been emphasized in Chapter XIV Section 134-136F of its Consolidated Administrative Order 2010-21. The Social Development and Management Program (SDMP) is mandated to be implemented by all operating mining/quarrying companies to support the education, health, social, cultural and economic aspects in the host communities. Since its implementation in 2011, it was noted that there are inconsistencies in the implementation of the Program. Thus, this research provided the necessary framework and recommendations to help just completed Programs and eventually improve the existing implementation of SDMP of mining companies. The concurrent triangulation mixed-methods research design was utilized wherein both the qualitative and quantitative approaches were simultaneously analyzed. Survey questionnaires were administered to an estimated 376 respondents from the host communities during site visits. In addition, interview and FGD were conducted to the various community representatives of the same. The results are the basis of a policy framework to help improved and reach its objectives to create self-reliant and resources-based communities.